MENINGKATKAN KEMAMPUAN SISWA MEMAHAMI MATERI DNA, RNA DAN SINTESA PROTEIN DENGAN METODE BERMAIN PADA PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 MUARO JAMBI - Rosni Rani Sitompul (Universitas Batanghari Jambi, 2015)
The low of students ability to understand the biology materials is abstract at grade XII IPA this indicate by the score everage class are under SKBM 60,this made the author did this research. Biology material at grade XII is abstract material its protein synthetic.In learning activity , biside students factor teacher factor and the way of teaching are also infhience outcome Throught the method that has been used in doing the learning activities.This research used playing method with DNA,RNA set in increasing students ability in protein synthetic materials.This research has been done in 2 cycles at grade XII IPA 1.This playing method is not only used it’s self but also it accompanied by other method like lecture and playing method.Playing method wich has been used in this research is past of role play method.through this playing method,students learn to understand the protein synthetic of their experience by doing the game activity by them selfes.Base on the outcome the analysis data shown that there is an increase of learning outcome. At the first cycle ,the mastery test score only 12.5% with the everage 37.8,while the second cycle increased to 84.2% with the everage score 66.1 .The students activity also increased with the everage score is enough in the first cycle be came excellent in the second cycle. Keywords : Playing method, Protein synthetic.